All from a walnut - Paquette, Ammi-Joan (Abrams Books for Young Readers, 2022)
Following a family tradition, Grandpa gives Emilia a walnut and together they plant and care for it, but as her little nut grows into a tree, Grandpa begins to slow down until one sad day Emilia has to say goodbye.